Analysis of BCA and Mandiri User Satisfaction Based on Google Maps and Google Play Store Reviews Using the Support Vector Machine Method - Alfianas Shofi Tafta Mahendra; Fajar Nugraha; Andy Prasetyo Utomo (Universitas Budi Luhur, 2026)
The development of digital banking services encourages banks to improve service quality through branch offices and mobile banking applications. User reviews on Google Maps and Google Play Store can be used to identify users’ assessments of these services. However, previous studies have generally focused on a single banking application or one review platform, so comparisons of branch and mobile banking services across two banks remain limited. This study aims to analyze sentiment, compare user satisfaction with BCA and Mandiri, and evaluate the performance of the Support Vector Machine (SVM) based on reviews from both platforms. The research stages include data collection, preprocessing, feature extraction using Term Frequency-Inverse Document Frequency, and sentiment classification using SVM. The dataset consists of 1,934 Google Maps reviews and 5,786 Google Play Store reviews. Testing results on Google Maps data achieved an accuracy of 91.99%, precision of 93.09%, recall of 98.25%, and F1-score of 95.60%. Meanwhile, testing on Google Play Store data achieved an accuracy of 83.85%, precision of 87.17%, recall of 77.96%, and F1-score of 82.31%. Sentiment analysis showed that positive sentiment toward BCA and Mandiri on Google Maps reached 87.79% and 88.96%, respectively. On Google Play Store, BCA Mobile obtained 43.68% positive sentiment, while Livin’ by Mandiri obtained 52.74%. Therefore, Mandiri had a higher proportion of positive sentiment on both platforms. This study contributes an integrated comparison of branch and mobile banking services and an evaluation of SVM performance across two different review sources.